PENGARUH TOTAL QUALITY MANAGEMENT (TQM) DAN SISTEM REWARD TERHADAP KINERJA PERUSAHAAN MANUFAKTUR (STUDI EMPIRIS PADA DIVISI FILTER PT. FSCM MANUFACTURING INDONESIA, KABUPATEN SIDOARJO) - NURUL W, ALIFIYAH (Jurnal Akuntansi AKUNESA, 2017)
Increased demaind for filter product in four-wheel vehicle becomes the opportunities for filter company to maximize profit and compete. However, it can be an obstacle because the company’s inability to meet demand and macth the quality, so need to increase the production line, in addition improved performance of the company. Good performance can be influed by several factors such as the implementation of TQM and reward system, the study aims to determine the influence of the implementation of TQM and reward system on the performance of PT FSCM Manufacturing Indonesia, Sidoarjo. Data collection techniques obtained directly by distributing questionnaires to 35 resondens with a simple random sampling method. Data analysis tools using SPSS 23 with multiple regression method. The research proves that there is a positive significant effect of the application of TQM in the company’s performance, and there is no influence between the reward system in the company’s performance. Keywords: The Company’s Performance, Reward System, Total Quality Management